Population dynamics and growth rates of the brown mussel (Perna perna) on wave exposed and wave sheltered shores of South Africa - Lindsay, Tracy Lynn (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 1999)
Population dynamics of Perna perna in low shore mussel beds were investigated over a 15 month period at six sites along the south coast of South Africa, with particular reference to the effects of wave exposure. The degree of exposure was first quantitatively ascertained using the dissolution of cement blocks to measure average wave force and dynamometers to measure maximum wave force. The mean mass loss of the cement blocks was higher at Diaz Cross and Kwaai Hoek than at Mgwalana, Rufanes and Riet River. No data were available for Fish River. The mean maximum wave force encountered at Diaz Cross, Kwaai Hoek and Fish River was significantly higher (p<O.05) than that at Mgwalana, Rufanes and Riet River. These results allowed the former sites to be classified as exposed and the latter as sheltered. Early recruitment (1-5 mm) occurred throughout the year, but peaked significantly (p<0.05) from January 1995 to May 1996 on both shore types. Although mean recruit density (1-15 mm) was Significantly higher at the exposed (5 896.mâ »Â²) than the sheltered shores (2 986.mâ »Â²), some sites did not show this trend. Further investigation revealed that the densities of recruits (1-5 & 6-10 mm) were significantly higher on algae than on mussels (p<0.05). Adult densities (>15 mm) were positively correlated with recruit densities (1-5 mm) for both shore types (p<O.05). In tum, adult density (>15 mm) was significantly lower on exposed (mean of 3 348.mâ »Â²) than on sheltered shores (mean of 4 796.mâ »Â²) (p<O.05). Adult mussels on exposed shores had significantly higher mean and maximum lengths than those on sheltered shores (p<O.05). Biomass, which is a product of density and length, showed no significant difference between the two shore types (p>O.05). The effect of exposure on growth rate formed the focal point of this study and was determined using three different approaches. The first technique, mark-recapture, involved filing notches on the growing edges of mussels in the field. After 111 days, mussels were removed and the growth measured. The second approach used internal growth bands to measure growth rates, once the periodicity with which these bands were laid down was established. Thirdly, using Shepherd's length composition analysis (SLCA), growth rates were determined from length frequency distributions in 11 samples taken over 15 months. The general conclusion from all three approaches was that growth rate was twice as fast on the exposed shores as on the sheltered shores (p<O.05). A mean length (averaged from all three methods) of 47.06 mm was attained within the first year of growth at the exposed shores and 22.07 mm at the sheltered shores. There were however considerable differences among these approaches. The mark-recapture method predicted the lowest growth rates, followed by growth band method and lastly SLCA. The mean mortality index (Z.yearâ »Â¹) for mussels was significantly (p<0.05) higher at the exposed shores (Z=1.81) than at the sheltered shores (Z=0.73). Consequently, the percentage survival rates per annum of mussels of all ages (total), 18 days to 6 months (juveniles) and 12 months to mortality (adults) was lower on the exposed than the sheltered shores. The survival rate of juveniles was as low as 0.71% per annum on the exposed shores and 9.29% per annum on the sheltered shores. The adult survival rate of exposed shore mussels was 11.78% per annum, considerably lower than that of sheltered shore mussels, 48.05%. The turnover rate on exposed shores was faster than on sheltered shores as the mean longevities were 2.6 and 6.7 years respectively. In conclusion, these findings showed that the effects of exposure on recruitment, growth and mortality are important in low shore mussel beds.
Keywords: Perna -- South Africa; Mussels -- South Africa